Eksploitasi Klaim Berlebihan dalam Etika Pemasaran dan Implikasi Hukum terhadap Perlindungan Konsumen - Putri Dewi Renggani; Halimah Zahrah; Dwi Julyansyah; Andyka Maulana Prayoga; Mia Damayanti (PENG: Jurnal Ekonomi dan Manajemen, 2025)
The growth of the skin care industry in the digital era has encouraged the emergence of various aggressive promotional strategies, including overclaim practices in product advertisements. This study aims to examine the form, impact, and ethical and legal implications of overclaiming practices in skincare product advertisements in Indonesia. Using a descriptive qualitative approach based on a literature study, this research examines seven scientific articles as well as relevant legal regulations to identify patterns of irregularities in the promotion of skin care products. The results of the analysis show that overclaims not only violate the principles of marketing ethics such as honesty, transparency, and social responsibility, but also contradict the provisions of consumer protection law, particularly Law Number 8 Year 1999 and BPOM Regulations. This is reinforced by weak supervision of digital promotions and the involvement of influencers without validation of information. This research emphasizes the importance of strengthening regulations, increasing consumer literacy, and enforcing business ethics in building a fair and accountable marketing ecosystem in the beauty industry.